Dietary Differences in Health Sciences Students - Mirela Lisičić Konaković; Sabina Šečić-Selimović; Arzija Pašalić; Nihad Fejzić; Irena Drmić Hofman; Amina Šeta; Ljerka Ostojić; Ivan Čavar; Lutvo Sporišević; Antonela Matana; Mario Marendić; Anes Jogunčić; et al. (Journal of Health Sciences)
Introduction: The impact of nutrition on human health has become a central topic in modern research. The Mediterranean diet, rich in fruits, vegetables, fish, whole grains, and olive oil, has been associated with a lower risk of cardiovascular diseases. However, the effects of non-Mediterranean diets, particularly among students, remain insufficiently explored. This study aimed to examine differences in the dietary habits of health sciences students in two cities in Bosnia and Herzegovina (Mostar and Sarajevo) and Split, Croatia.